2011
DOI: 10.1371/journal.pone.0026061
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Fatigue Severity in Early Systemic Sclerosis: A Prospective Longitudinal Study of the GENISOS Cohort

Abstract: ObjectivesLongitudinal studies examining the baseline predictors of fatigue in SSc have not been reported. Our objectives were to examine the course of fatigue severity over time and to identify baseline clinical, demographic, and psychosocial predictors of sequentially obtained fatigue scores in early SSc. We also examined baseline predictors of change in fatigue severity over time.MethodsWe analyzed 1090 longitudinal Fatigue Severity Scale (FSS) scores belonging to 256 patients who were enrolled in the Genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…3,8,10 It has been reported that the greatest impairment in SF-36 subscale scores of SSc patients appeared to be in the physical functioning, general health, and role physical domains whereas mental health was relatively preserved. 9,10 The authors suggested that this unexpected high result in mental summary score was due to psychological adaptation and coping with chronic and disabling underlying conditions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3,8,10 It has been reported that the greatest impairment in SF-36 subscale scores of SSc patients appeared to be in the physical functioning, general health, and role physical domains whereas mental health was relatively preserved. 9,10 The authors suggested that this unexpected high result in mental summary score was due to psychological adaptation and coping with chronic and disabling underlying conditions.…”
Section: Resultsmentioning
confidence: 99%
“…1,6 A 0-100 mm breathing visual analog scale was used to measure self-assessment of breathlessness. 1,3,8 Fatigue severity scale was used to measure the impact of excessive fatigue on daily function. 14 The scale includes nine questions related to how fatigue interferes with certain activities, and rates its severity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations